1982
DOI: 10.1093/oxfordjournals.aje.a113335
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic Heterogeneity of Neural Tube Defects: Clues From Epidemiology1

Abstract: The epidemiology of neural tube defects was reviewed, using data from two birth defects surveillance systems: the nationwide Birth Defects Monitoring Program and the Metropolitan Atlanta Congenital Defects Program, for 1970-1978 and 1968-1979, respectively. After excluding cases with recognized causes, neural tube defects were divided into two major groups: "singles" and "multiples," depending on the presence of associated major defects. Only singles, which accounted for the majority of cases, were shown to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
98
1
2

Year Published

1985
1985
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(110 citation statements)
references
References 0 publications
9
98
1
2
Order By: Relevance
“…7,11,12 This is relevant, as the various neural tube defects are anatomically distinct and can have different etiologies. 13,14 Our results are consistent with the findings of other authors. Wasserman et al measured social indicators at the individual and community level and found higher risks of ARP ϭ acute risk period, defined as the period from three months prior to conception to one month after conception…”
Section: Discussionsupporting
confidence: 93%
“…7,11,12 This is relevant, as the various neural tube defects are anatomically distinct and can have different etiologies. 13,14 Our results are consistent with the findings of other authors. Wasserman et al measured social indicators at the individual and community level and found higher risks of ARP ϭ acute risk period, defined as the period from three months prior to conception to one month after conception…”
Section: Discussionsupporting
confidence: 93%
“…In 1982, Khoury et al found this incidence to be 12% from the Center for Disease Control (CDC) nationwide and 20% from the Atlanta Surveillance Systems [17]. It is difficult to compare our results with these studies as we have no records of the associated congenital anomalies in cases of anencephaly.…”
Section: Discussionmentioning
confidence: 64%
“…Thaliji et al from the eastern province of Saudi Arabia found that 15% of all cases of neural tube defects were associated with other congenital defects [17]. In 1982, Khoury et al found this incidence to be 12% from the Center for Disease Control (CDC) nationwide and 20% from the Atlanta Surveillance Systems [17].…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant associations were found for total trihalomethanes and with perchloroethylene and nitrates, when the data were adjusted for the confounding effects of total trihalomethanes. Craun (51) (14), supported by earlier discussions of the heterogeneity of NTDs (3,4,6), establishes clearly the necessity of, at a minimum, assessing anencephaly and spina bifida separately when attempting to identify environmental etiologic agents. If, in fact, these two defects have distinct embryologic bases, as the evidence for the multisite closure model suggests (14), then lumping them together would represent outcome misclassification that would tend to reduce any association between an environmental agent and one of the defects toward the null.…”
Section: The Environment and Neural Tube Defectsmentioning
confidence: 88%
“…Early discussions focused on the importance of looking at defects associated with chromosomal or genetic factors separately from those expected to be due to multifactorial etiology (3)(4)(5). Later discussions focused on epidemiologic differences between anencephaly and spina bifida (6) and on potential etiologic differences between NTDs with and without malformations in other organ systems-often referred to as single versus multiple (7)(8)(9) and upper versus lower NTDs (10,11).…”
Section: Heterogeneity Of Neural Tube Defectsmentioning
confidence: 99%